APPROACH TO RELIABILITY ANALYSIS OF THE COMPUTER NETWORK FUNCTIONING OF THE MANAGEMENT SYSTEM - Konovaliuk, Valentyna; Klyus, Iryna (Proceedings of National Aviation University (archive), 2015)
The article considers a mathematical model of information technologies management systems in order to calculate steady-state measures of performance.